Spatiotemporal evolution and multi-scenario simulation of the land-use cover change and habitat quality in arid and semi-arid areas: a case study of the urban agglomeration along the Yellow River in Ningxia, China - Ma, Tianle; Cheng, Wenhao; Yao, Wenxuan (Frontiers in Environmental Science, 2025)
Habitat quality (HQ) is recognized as a significant factor in biodiversity maintenance and ecological conservation advancement, and the land-use cover change (LUCC) can directly affect the spatial pattern and evolution of HQ. Land-use datasets spanning 2010, 2015, and 2020 were analyzed through the integrated application of the future land-use simulation (FLUS) model and the integrated valuation of ecosystem services and trade-offs (InVEST) model, supplemented by multiple analytical indicators, resulting in LUCC patterns and HQ variations being investigated within the urban agglomeration along the Yellow River in Ningxia, China. These findings demonstrate (Hall, Wiley on behalf of the Wildlife Society, 1997, 25(1), 173–82) a reduction in ecological land coverage during the previous period, which correlates with a decrease in the mean HQ. The value ratings in 2010, 2015, and 2020 were 0.4919, 0.4730, and 0.4654, respectively. Moreover, the evolution characteristics exhibited distinct divergence trends between the periods of 2010–2015 and 2015–2020. The spatial distribution showed a pronounced periphery–core gradient (Fahrig, Eution, and Systematics, 2017, 48(1), 1–23). The study area’s HQ was categorized within the moderate-to-good range, with mean values demonstrating a descending sequence: EPS (0.5348) > NDS (0.5165) > FSS (0.4967) > EDS (0.4681). Optimal ecosystem service performance was observed in the Helan Mountain Nature Reserve and Yellow River mainstream (Alaniz et al., Ecological Indicators, 2021, 126). Scenario modeling revealed that ecological conservation measures effectively enhanced biodiversity preservation and ecosystem service capacity. Scenario optimization was determined through the combined evaluation of ecological resource support limit and territorial development suitability. Multi-scenario methods and environmental simulation models were integrated in this study, enabling a more accurate assessment of the landscape spatiotemporal pattern. This approach provides decision-making insights and multiple perspectives for spatial planning under different developmental goal orientations.